Control method for chambering steel inclusions

Through converter, LF refining, RH vacuum refining and continuous casting processes, combined with argon station pre-reduction, titanium-aluminum-oxygen composite oxide formation and high temperature gradient control, the vermiculite mid-cover cover agent was used to solve the effect of inclusions in the pore-rejuvenating steel. The problem of this paper significantly reduces the number and size of inclusions, improves the porosity and the forming performance of the steel plate.

CN119287105AActive Publication Date: 2025-01-10МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411246503.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-10
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the size of inclusions in the reaming steel through the steel production process combination without additional materials, resulting in the reaming rate being affected and the reaming cracking problem occurs.

Method used

Using converter, LF refining, RH vacuum refining and continuous casting processes, the mass percentage of N in steel is controlled ≤0.0040%, and white slag is formed through pre-reduction of the argon station, titanium-aluminum-oxygen composite oxide is formed in LF, and medium and high vacuum degree of RH Dehydrogenation and addition of ferroilium alloy, combined with high temperature gradient controlled crystallizer cooling, vermiculite mid-covering agent is used to reduce inclusion quantity and size.

Benefits of technology

The number and size of Al2O3, Ti2O3-Al2O3-CaS and TiN-type inclusions are significantly reduced, the incidence of reaming and cracking caused by inclusions is reduced, and the porosity reaming and forming performance of the steel plate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287105A_ABST
    Figure CN119287105A_ABST
Patent Text Reader

Abstract

The invention provides a control method for chambering steel inclusions. The control method comprises the following steps of converter treatment, LF refining, RH vacuum refining and continuous casting. The mass percentage content of N in the chambering steel is less than or equal to 0.0040%. According to the method, a tapping-argon station-LF furnace three-in-one reduction slagging process is adopted, two-step ferrotitanium alloying is performed, and vacuum pre-calcium treatment is assisted, so that Al2O3 inclusion denaturation is more thorough, and the number of B-class and DS-class inclusions in steel is smaller. According to continuous casting of the method, the cooling strength of the crystallizer is controlled through the high temperature gradient, the temperature gradient of the solidification front edge is improved, and the obtained precipitates are smaller in size. According to the control method for the inclusions of the reaming steel, the number and the size of B-type inclusions such as Al2O3 and Al2O3-MgO, DS-type inclusions such as Al2O3-CaO with the content ratio of Ti2O3-Al2O3-CaS to aluminum and calcium being 0.8-1.5 and TiN-type inclusions are remarkably reduced, and the problem of reaming cracking caused by the inclusions is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of off-furnace refining, and in particular to a method for controlling inclusions in hole-expanding steel. Background Art

[0002] Hole expansion steel requires high tensile strength, good formability and flange flanging performance. Hole expansion rate, as a formability index of hole expansion steel, reflects the ability of the steel plate to resist local cracking in the direction perpendicular to the hole edge due to excessive local elongation deformation of the hole edge during the hole expansion process. The larger the hole expansion rate, the greater its fatigue resistance and the better the hole expansion performance.

[0003] One of the factors that has a greater impact on hole expansion performance is the number, type and size of inclusions in steel. Among them, the inclusions that are most harmful to hole expansion rate are Class B, Class D and Class DS inclusions. In the new version of "Standard Rating Chart Microscopic Inspection Method for Determination of Non-metallic Inclusions in Steel" (GB / T10561-2023), TiN inclusions can also be compared with Class B, Class C, Class D and Class DS inclusions based on their morphology, and their chemical characteristics are indicated by the following subscripts. For example, a high hole expansion steel produced by a factory using the LF+RH refining process cracked during hole expansion by the user, and physical dissection found (such as Figure 1 As shown in the figure, there are Al2O3 and Al2O3-MgO inclusions with a size larger than 17μm, Ti2O3-Al2O3-CaS with a size larger than 27μm, and Al2O3-CaO with an aluminum-calcium content ratio of 0.8 to 1.5, etc., which are DS inclusions with a rating of more than 1.0, and there are also TiN inclusions with a size larger than 10μm, composed of a single or multiple TiNs. In order to solve the problem of large-sized B-type and DS-type inclusions affecting hole expansion, it is necessary to propose a targeted control method.

[0004] In order to improve the hole expansion rate, metallurgical workers have made a lot of research. For example, the Chinese patent application with publication number CN108048734A discloses a 700MPa tensile strength hot-rolled complex phase steel and its production method. The method adds rare earth elements RE in the composition design to optimize the shape and size of inclusions in the steel, thereby improving the hole expansion rate of the steel. The Chinese patent application with publication number CN117802419A discloses a 1.0GPa-grade hydrogen embrittlement-resistant cold-rolled CH steel and its preparation method. By controlling the Mg element content at 0.005-0.50%, the carbide size and distribution of DH steel are improved. The Chinese invention patent with authorization announcement number CN114107792B discloses a 780MPa-grade high surface ultra-high hole expansion steel and its manufacturing method, pointing out that in the steelmaking process, the Mg deoxidation method is adopted to preferentially form dispersed fine MgO in the molten steel, creating more nucleation points for the formation of TiN in the subsequent continuous casting process, which can effectively refine TiN particles and improve the stability of the hole expansion rate.

[0005] However, most of the existing technologies optimize the shape and size of inclusions in steel by adding rare earth elements or magnesium treatment, and there are few inclusion control methods that can meet the hole expansion rate requirements through the process combination of the hole expansion steel production process itself without adding additional materials. Summary of the invention

[0006] In order to overcome the shortcomings of the above-mentioned technology, the purpose of the present invention is to provide a method for controlling inclusions in hole expansion steel, reduce the size of inclusions, thereby reducing the impact of inclusions on hole expansion rate, and solve the problem of hole expansion cracking caused by inclusions.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for controlling inclusions in hole-expanding steel comprises the following steps: obtaining hole-expanding steel ingots by converter, LF refining, RH vacuum refining and continuous casting; and controlling the mass percentage of N in the steel product to be ≤0.0040%.

[0009] Preferably, during the converter process, the carbon content of the converter at the end of the main blowing is ≥ 0.30% (weight percentage) to ensure that a good amount of carbon-oxygen reaction can be maintained during the auxiliary blowing period to reduce the intake of the furnace mouth; during the auxiliary blowing, the bottom blowing argon intensity is increased to 0.12-0.16Nm 3 / (ton liquid·min), forming a local area argon bubble vacuum to promote the escape of N2; aluminum particles, lime and bauxite are added during the converter tapping. Among them, ton liquid·min is per ton liquid per minute, and the liquid is all the liquid in the furnace, including molten steel and slag in liquid form.

[0010] Preferably, after the converter is tapped, strong argon blowing is performed through an argon station to pre-reduce the slag and maintain good spreadability, thereby achieving early slag reduction and rapid formation of white slag; the intensity of the strong argon blowing is 2.0 to 4.0 standard liters / (minute·ton of steel).

[0011] Preferably, the total number of heating times during the LF refining process is controlled at 2 to 3 times, and the first, second and third heating temperature rise times are controlled in steps according to the initial temperature, the first heating time is 10 to 16 minutes, the second heating time is 6 to 8 minutes, and the third heating time is 4 to 6 minutes. Compressed air is passed through the ladle cover to maintain a slight positive pressure in the furnace so as not to emit thick smoke.

[0012] Preferably, during the LF refining process, after the LF forms white slag and is maintained for 15 minutes, the temperature is measured and the oxygen is determined, the temperature of the molten steel is maintained at 1590-1605°C, the active oxygen of the molten steel is 10-30ppm, the slag surface is blown open and titanium-iron alloy is added, and after medium-intensity bottom blowing of argon and stirring for 3 minutes, aluminum particles are added for final deoxidation and alloying. Among them, the amount of titanium-iron alloy added is 40-50% of the total weight of titanium-iron alloy added, and the amount of aluminum particles added is the total amount required for the steel grade. The intensity of medium-intensity bottom blowing of argon is 0.20-1.0 standard liters / (minute·ton of steel). The purpose is to first allow a part of the titanium-iron to undergo oxidation reaction to generate fine titanium oxide, and then polymerize with the subsequent aluminum oxide inclusions in the molten steel to form titanium-aluminum-oxygen composite oxide. This type of titanium-aluminum-oxygen composite oxide has a small wetting angle and is easy to separate from the molten steel. It can be removed in the subsequent long-term RH vacuum cycle refining process, thereby reducing the number of inclusions in the steel.

[0013] Preferably, in the later stage of LF refining, after all components except Ti element are qualified, weak stirring is carried out for 3 to 5 minutes, and then pure calcium wire is fed. After feeding pure calcium wire, the mass percentage of Ca in molten steel is 20 to 50 ppm. After feeding the wire, go directly to the RH station for vacuum refining. Among them, the weak stirring bottom argon blowing intensity is 0.02 to 0.35 standard liters / (minute·ton of steel). After RH adopts high vacuum to meet the dehydrogenation requirements, the remaining titanium-iron alloy is added and the content of elements such as Ti, Als, and Mn is fine-tuned to the content requirements of the steel grade. The purpose of this is to make the Al2O3 inclusions more thoroughly denatured and the number of Class B and DS inclusions in the steel less.

[0014] Preferably, the RH vacuum refining uses high vacuum to meet the requirements of dehydrogenation, and then adds the remaining titanium-iron alloy, and then uses low vacuum large circulating gas to perform the denitrification function, drives the gas flow to the maximum capacity of the equipment, and fine-tunes the content of elements such as Ti, Als, and Mn to the requirements of the steel grade component content; the vacuum degree of the high vacuum dehydrogenation process is <67Pa; the vacuum degree of the low vacuum circulation process is 1~5kpa.

[0015] Preferably, a high temperature gradient is used to control the cooling intensity of the crystallizer during the continuous casting process, and the actual crystallizer cooling effect is monitored by the hot surface temperature measured by the thermocouples of the first row of copper plates in the crystallizer and the heat flux density of the narrow copper plates on both sides of the crystallizer. The hot surface temperature measured by the thermocouples of the first row of copper plates in the crystallizer is controlled at 90-125°C, and the difference in heat flux density of the narrow copper plates on both sides of the crystallizer is controlled at 0-0.06MW / mm 2 The purpose of this is to make the temperature of the ingot at the outlet of the crystallizer 50 to 100°C lower than the ingot temperature under traditional cooling intensity, increase the temperature gradient at the solidification front, inhibit the precipitation and growth of titanium nitride inclusions, and obtain a smaller precipitate size.

[0016] Preferably, in addition to the conventional protective pouring, the continuous casting step uses a tundish covering agent containing 5-10% (by weight) vermiculite, because vermiculite has good heat preservation and spreadability, so as to avoid nitrogen increase caused by cracking of the tundish slag crust and leakage of air.

[0017] Preferably, the hole-expanding steel is HR600 / 780HE hole-expanding steel, and the mass percentage of N in the steel is ≤0.0040%.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention provides a method for controlling inclusions in hole expansion steel, which significantly reduces the number and size of B-type inclusions such as Al2O3 and Al2O3-MgO, DS-type inclusions such as Ti2O3-Al2O3-CaS and Al2O3-CaO with an aluminum-calcium ratio of 0.8 to 1.5, and TiN-type inclusions, and ultimately reduces the incidence of hole expansion cracking caused by inclusions.

[0020] The method of the present invention adopts a tundish covering agent containing 5 to 10% (weight percentage) of vermiculite as a nitrogen control measure throughout the entire process, so as to avoid nitrogen increase caused by cracking of the tundish slag crust and leakage of air. The method of the present invention adopts a three-in-one reduction slag-making process of steel-outlet-argon station-LF furnace, two-step titanium-iron alloying and auxiliary calcium treatment before vacuum, so that the Al2O3 inclusions are more thoroughly denatured and the number of B and DS inclusions in the steel is less. The continuous casting of the method of the present invention adopts a high temperature gradient to control the cooling intensity of the crystallizer, improve the temperature gradient of the solidification front, and obtain a smaller precipitate size. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic diagram of inclusions in hole-expanding steel produced by a steel plant. Figure 1 a is an Al2O3-CaO inclusion in steel with a size of 37.1 μm and an aluminum-calcium ratio of 0.8 to 1.5; Figure 1 b is Ti2O3-Al2O3-CaS inclusions in steel with a size larger than 27.6 μm;

[0022] Figure 2 It is a comparison diagram of the types of inclusions in the tundish steel liquid of Comparative Example 1 and Example 1;

[0023] Figure 3 This is a comparison chart of the steel plate inclusion types of Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0024] In order to better explain the present invention, the main contents of the present invention are further explained below in conjunction with specific embodiments, but the contents of the present invention are not limited to the following embodiments.

[0025] Example 1

[0026] The smelting steel type is HR600 / 780HE hole-expanding steel, and the inclusion control method steps include converter, LF refining, RH vacuum refining and continuous casting.

[0027] During the converter process, the carbon content at the end of the converter main blowing was 0.42% (weight percentage), and the bottom blowing argon intensity during auxiliary blowing was 0.14Nm 3 / (ton liquid·min). Aluminum particles, lime and bauxite are added to the converter steel, and the argon station performs strong argon blowing to pre-reduce the slag.

[0028] During LF refining, LF is heated twice in total, and the heating time for the two times is 16min and 7min, and the furnace is kept at a slightly positive pressure. After LF forms white slag and maintains it for 15min, the temperature and oxygen are measured, the molten steel temperature is 1596℃, and the active oxygen of the molten steel is 12ppm. Then the slag surface is blown open and titanium-iron alloy with a titanium content of 70% is added, and the addition amount is 0.71kg / t steel. After medium-intensity bottom blowing argon and stirring for 3min, aluminum particles are added for final deoxidation and alloying; in the later stage of LF refining, weak stirring is carried out for 3min after all components except Ti element are qualified. LF is fed with 420 meters of pure calcium wire. After feeding the pure calcium wire, the mass percentage of Ca in the molten steel is between 32ppm. After feeding the wire, go directly to the RH station for vacuum refining.

[0029] In RH vacuum refining, after dehydrogenation with high vacuum (<67Pa), the remaining ferro-titanium alloy is added, and the content of each alloy element is fine-tuned to the content requirements of the steel grade using low vacuum cycle. The total RH cycle time (opening vacuum-breaking) is 25min, and the amount of remaining ferro-titanium alloy (titanium content is 70%) added is 0.95kg / t steel. The vacuum degree of the low vacuum cycle is 3kpa.

[0030] The continuous casting tundish covering agent is a tundish covering agent containing 7% (weight percentage) vermiculite. The hot surface temperature measured by the thermocouple of the first row of copper plates of the crystallizer is 120°C, and the heat flux density difference of the narrow copper plates on both sides of the crystallizer is 0.02MW / mm 2 .

[0031] Finally, HR600 / 780HE hole expansion steel was obtained, and the mass percentage of nitrogen in the steel was 0.0032%.

[0032] like Figure 2 As shown in b, among the inclusions in the tundish steel liquid, the components of the inclusions are relatively uniform, the Al2O3 is fully modified, and the main inclusions are Al2O3-CaO inclusions.

[0033] like Figure 3 As shown in b, in the steel plate sample obtained after hot rolling of the ingot, the number of inclusions is small, the component composition is relatively concentrated, and there are no independent CaS inclusions and Al2O3-CaS inclusions.

[0034] Class B inclusions are rated 0-0.5, and Class D and DS inclusions are rated 0-0.5. The size of Al2O3 and Al2O3-MgO inclusions in steel is 3.25-7.34μm, with an average of 4.42μm, and the number accounts for 0.87% of the total number of inclusions. The size of Ti2O3-Al2O3-CaS inclusions is 3.26-10.23μm, with an average of 4.04μm, and the number accounts for 11.21% of the total number of inclusions. The size of Al2O3-CaO inclusions with an aluminum-calcium ratio of 0.8-1.5 is 4.43-5.27μm, with an average of 4.99μm, and the number accounts for 0.35% of the total number of inclusions.

[0035] As shown in Table 1, the number density of oxide inclusions in the above steel plate sample is 4.89 / mm 2 , the size range is 2.68~11.01μm, the average size is 4.54μm, and there is no oxide inclusion larger than 13μm; the number density of TiN inclusions is 12.83 / mm 2 The size range is 0.87 to 9.00 μm, the average size is 4.09 μm, and the proportion of TiN inclusions larger than 8 μm is 0.78%.

[0036] The hole expansion ratio of the finally obtained HR600 / 780HE hole-expanded steel plate is 56-85%, and the cracking occurrence rate is 0.3%.

[0037] Example 2

[0038] The smelting steel type is HR600 / 780HE hole-expanding steel, and the inclusion control method steps include converter, LF refining, RH vacuum refining and continuous casting.

[0039] During the converter process, the carbon content at the end of the converter main blowing was 0.37% (weight percentage), and the bottom blowing argon intensity during auxiliary blowing was 0.14Nm 3 / (ton liquid·min). Aluminum particles, lime and bauxite are added to the converter steel, and the argon station performs strong argon blowing to pre-reduce the slag.

[0040] During LF refining, LF is heated twice in total, and the heating time for the two times is 14min and 8min, and the furnace is kept at a slightly positive pressure. After LF forms white slag and maintains it for 15min, the temperature and oxygen are measured, the molten steel temperature is 1597℃, and the active oxygen of the molten steel is 18ppm. Then the slag surface is blown open and titanium-iron alloy with a titanium content of 70% is added, and the addition amount is 0.73kg / t steel. After medium-intensity bottom blowing argon and stirring for 3min, aluminum particles are added for final deoxidation and alloying; in the later stage of LF refining, weak stirring is carried out for 3min after all components except Ti element are qualified. LF is fed with 432 meters of pure calcium wire. After feeding the pure calcium wire, the mass percentage of Ca in the molten steel is between 29ppm. After feeding the wire, go directly to the RH station for vacuum refining.

[0041] In RH vacuum refining, after dehydrogenation with high vacuum (<67Pa), the remaining ferro-titanium alloy is added, and the content of each alloy element is fine-tuned to the content requirements of the steel grade using low vacuum cycle. The total RH cycle time (opening vacuum-breaking) is 24 minutes, and the amount of remaining ferro-titanium alloy (titanium content is 70%) added is 0.93kg / t steel. The vacuum degree of the low vacuum cycle is 2.7kpa.

[0042] The continuous casting tundish covering agent is a tundish covering agent containing 7% (weight percentage) vermiculite. The hot surface temperature measured by the thermocouple of the first row of copper plates of the crystallizer is 118°C, and the heat flux density difference of the narrow copper plates on both sides of the crystallizer is 0.015MW / mm 2 .

[0043] Finally, HR600 / 780HE hole expansion steel was obtained, and the mass percentage of nitrogen in the steel was 0.0029%.

[0044] In the steel plate samples obtained after hot rolling of the ingot, the B-type inclusions were rated 0-0.5, and the D-type and DS-type inclusions were rated 0-0.5. The size of Al2O3 and Al2O3-MgO inclusions in the steel was 3.25-7.39μm, with an average of 4.21μm, and the number accounted for 0.16% of the total number of inclusions. The size of Ti2O3-Al2O3-CaS inclusions was 3.26-10.03μm, with an average of 4.14μm, and the number accounted for 9.21% of the total number of inclusions. The size of Al2O3-CaO inclusions with an aluminum-calcium ratio of 0.8-1.5 was 4.43-5.52μm, with an average of 4.87μm, and the number accounted for 0.21% of the total number of inclusions.

[0045] As shown in Table 1, the number density of oxide inclusions in the above steel plate sample is 3.37 / mm 2 , the size range is 1.02~12.51μm, the average size is 3.65μm, and there is no oxide inclusion larger than 13μm; the number density of TiN inclusions is 12.34 / mm2 The size range is 1.0 to 9.18 μm, the average size is 4.32 μm, and the proportion of TiN inclusions larger than 8 μm is 1.14%.

[0046] The HR600 / 780HE expanded steel plate finally obtained has a hole expansion ratio of 53-81% and no cracking.

[0047] Example 3

[0048] The smelting steel type is HR600 / 780HE hole-expanding steel, and the inclusion control method steps include converter, LF refining, RH vacuum refining and continuous casting.

[0049] During the converter process, the carbon content at the end of the converter main blowing was 0.33% (weight percentage), and the bottom blowing argon intensity during auxiliary blowing was 0.15Nm 3 / (ton liquid·min). Aluminum particles, lime and bauxite are added to the converter steel, and the argon station performs strong argon blowing to pre-reduce the slag.

[0050] During LF refining, LF is heated twice in total, and the heating time for the two times is 15min and 7min, and the furnace is kept at a slightly positive pressure. After LF forms white slag and maintains it for 15min, the temperature and oxygen are measured, the molten steel temperature is 1601℃, and the active oxygen of the molten steel is 21ppm. Then the slag surface is blown open and titanium-iron alloy with a titanium content of 70% is added, and the addition amount is 0.76kg / t steel. After medium-intensity bottom blowing argon and stirring for 3min, aluminum particles are added for final deoxidation and alloying; in the later stage of LF refining, weak stirring is carried out for 3min after all components except Ti element are qualified. LF is fed with 432 meters of pure calcium wire. After feeding the pure calcium wire, the mass percentage of Ca in the molten steel is between 29ppm. After feeding the wire, go directly to the RH station for vacuum refining.

[0051] In RH vacuum refining, after dehydrogenation with high vacuum (<67Pa), the remaining ferro-titanium alloy is added, and the content of each alloy element is fine-tuned to the content requirements of the steel grade using low vacuum cycle. The total RH cycle time (opening vacuum-breaking) is 24 minutes, and the amount of remaining ferro-titanium alloy (titanium content is 70%) added is 0.90kg / t steel. The vacuum degree of the low vacuum cycle is 3.5kpa.

[0052] The continuous casting tundish covering agent is a tundish covering agent containing 7% (weight percentage) vermiculite. The hot surface temperature measured by the thermocouple of the first row of copper plates of the crystallizer is 108°C, and the heat flux density difference of the narrow copper plates on both sides of the crystallizer is 0.018MW / mm 2 .

[0053] Finally, HR600 / 780HE hole expansion steel was obtained, and the mass percentage of nitrogen in the steel was 0.0031%.

[0054] In the steel plate samples obtained after hot rolling of the ingot, the B-type inclusions were rated 0-0.5, and the D-type and DS-type inclusions were rated 0-0.5. The size of Al2O3 and Al2O3-MgO inclusions in the steel was 2.01-6.37μm, with an average of 3.98μm, and the number accounted for 0.26% of the total number of inclusions. The size of Ti2O3-Al2O3-CaS inclusions was 3.26-9.3μm, with an average of 4.02μm, and the number accounted for 6.21% of the total number of inclusions. The size of Al2O3-CaO inclusions with an aluminum-calcium ratio of 0.8-1.5 was 3.41-9.52μm, with an average of 4.07μm, and the number accounted for 0.08% of the total number of inclusions.

[0055] As shown in Table 1, the number density of oxide inclusions in the above steel plate sample is 2.93 pieces / mm 2 , the size range is 2.01~17.1μm, the average size is 3.93μm, the proportion of oxide inclusions larger than 13μm is 0.08%; the number density of TiN inclusions is 11.03 / mm 2 The size range is 1.31 to 10.19 μm, the average size is 3.61 μm, and the proportion of TiN inclusions larger than 8 μm is 0.21%.

[0056] The HR600 / 780HE expanded steel plate finally obtained has a hole expansion ratio of 61-87% and no cracking.

[0057] Comparative Example

[0058] The steel type to be smelted is HR600 / 780HE hole expansion steel, and the method steps are converter, LF refining, RH vacuum refining and continuous casting.

[0059] The carbon content of the converter at the end of the main blowing was 0.12% (weight percentage), and the bottom blowing argon intensity was increased to 0.08Nm during the auxiliary blowing. 3 / (tons of liquid·min).

[0060] The total number of LF heating times is 4, and the heating time of the two heatings is 12min, 8min, 5min and 3min. After the LF forms white slag, all titanium-iron alloy (containing 70% titanium) is added in an amount of 1.66kg / t steel.

[0061] The total RH cycle time (opening pumping-breaking air) is 25 minutes. After breaking air, 450 meters of pure calcium wire is fed and then weakly stirred for 8 minutes. The Ca content in the steel is between 30ppm.

[0062] The continuous casting tundish covering agent is a common tundish covering agent. The hot surface temperature measured by the thermocouple of the first row of copper plates of the crystallizer is 132°C, and the heat flux density difference of the narrow copper plates on both sides of the crystallizer is 0.079MW / mm2 .

[0063] The mass percentage of nitrogen in the finally obtained HR600 / 780HE hole expansion steel is 0.0053%.

[0064] like Figure 2 As shown in a, in the inclusions in the tundish steel liquid, the components of the inclusions are dispersed, and there are magnesia-alumina spinel, insufficiently modified Al2O3 and Al2O3-CaO-MgO inclusions.

[0065] like Figure 3 As shown in a, the steel plate sample obtained after hot rolling of the ingot has a large number of inclusions, the composition of the inclusion components is relatively dispersed, and contains independent CaS inclusions.

[0066] Class B inclusions are rated 0 to 1.5, and Class D and DS inclusions are rated 0 to 2.0. The size of Al2O3 and Al2O3-MgO inclusions in steel is 2.69 to 20.12 μm, with an average of 7.89 μm; the number accounts for 4.7% of the total number of inclusions. The size of Ti2O3-Al2O3-CaS inclusions is 5.89 to 27.61 μm, with an average of 10.65 μm; the number accounts for 13.98% of the total number of inclusions. The size of Al2O3-CaO inclusions with an aluminum-calcium ratio of 0.8 to 1.5 is 6.83 to 37.1 μm, with an average of 12.31 μm; the number accounts for 0.96% of the total number of inclusions.

[0067] As shown in Table 1, the number density of oxide inclusions in the steel plate sample is 6.18 / mm 2 The size range is 3.01 to 27.01 μm, the average size is 5.61 μm, and the proportion of oxide inclusions larger than 13 μm is 2.72%; the number density of TiN inclusions is 13.72 / mm 2 The size range is 3.01 to 20.46 μm, the average size is 4.61 μm, and the proportion of TiN inclusions larger than 8 μm is 3.50%.

[0068] The final HR600 / 780HE hole-expanding steel plate has a hole-expanding rate of 35-62%. Customers reported cracking, and the cracking rate of the supply batch was about 5%.

Claims

1. A method for controlling inclusions in hole expansion steel, characterized in that: The following steps are involved: The hole-expanding steel ingot is obtained by converter, LF refining, RH vacuum refining and continuous casting; the mass percentage of N in the hole-expanding steel is ≤0.0040%.

2. The control method according to claim 1, characterized in that: In the converter step, the mass percentage of carbon in the molten steel is ≥0.30% when the converter main blowing is completed, and the bottom blowing argon intensity is 0.12-0.16Nm 3 / (tons of liquid·min); aluminum particles, lime and bauxite are added during the converter steelmaking process.

3. The control method according to claim 1, characterized in that: After the steel is tapped from the converter, strong argon blowing is carried out through an argon station to pre-reduce the slag.

4. The control method according to claim 1, characterized in that: In the LF refining process, the total number of heating times is controlled to be 2 to 3 times, and the heating time is controlled in steps according to the initial temperature. The first heating time is 10 to 16 minutes, the second heating time is 6 to 8 minutes, and the third heating time is 4 to 6 minutes.

5. The control method according to claim 4, characterized in that: During the LF refining process, after the LF furnace forms white slag and maintains it for 15 minutes, the temperature and oxygen are measured to control the molten steel temperature to 1590-1605°C and the active oxygen content of the molten steel to 10-30ppm. Subsequently, the slag surface is blown open and ferrotitanium alloy accounting for 40-50% of the total added mass of ferrotitanium alloy is added. After medium-intensity bottom blowing of argon and stirring, aluminum particles are added for final deoxidation and alloying.

6. The control method according to claim 4, characterized in that: During the LF refining process, after all components except Ti element are qualified, weak stirring is carried out for 3 to 5 minutes, and then pure calcium wire is fed. After feeding pure calcium wire, the mass percentage of Ca in molten steel is 20 to 50 ppm. After feeding pure calcium wire, it is directly sent to RH station for RH vacuum refining.

7. The control method according to claim 5, characterized in that: After high vacuum dehydrogenation, the remaining titanium-iron alloy is added in the RH vacuum refining, followed by low vacuum circulation and fine-tuning of the content of each alloy element to the steel grade component content requirement; the vacuum degree of the high vacuum dehydrogenation process is <67Pa; the vacuum degree of the low vacuum circulation process is 1-5kPa.

8. The control method according to claim 1, characterized in that: In the continuous casting process, a high temperature gradient is used to control the cooling intensity of the crystallizer, the hot surface temperature measured by the thermocouples of the first row of copper plates of the crystallizer is controlled at 90-125°C, and the heat flux density difference of the narrow copper plates on both sides of the crystallizer is controlled at 0-0.06MW / mm 2 .

9. The control method according to claim 1, characterized in that: The middle-package covering agent used in the continuous casting step contains vermiculite, and the weight percentage of the vermiculite in the middle-package covering agent is 5-10%.

10. The control method according to claim 1, characterized in that: The hole-expanding steel is HR600 / 780HE hole-expanding steel, and the mass percentage of N in the steel is ≤0.0040%.

Citation Information

Patent Citations

  • Methods for controlling inclusions in steel

    CN102268512A

  • Control method of iron-nickel-based superalloy inclusions

    CN115287396A

  • Method for controlling B-type inclusions in pipeline steel

    CN116516235A

  • Method for refining size of titanium nitride inclusion at core part of titanium-containing high-strength steel casting blank

    CN117344085A

  • Pipeline steel having excellent acid resistance property, and manufacturing method therefor

    WO2023103514A1